New Monoterpene Lactones from Actaea cimicifuga - Ma, Li-Juan; Wang, Yue-Hu; Tang, Gui-Hua; Wang, Ye-Ling; Ma, Chunhui; Dastmalchi, Keyvan; Kennelly, Edward J.; Long, Chun-Lin (Planta Medica, 2013)
Three new monoterpene lactones, cimicifugolides A−C (1–3), along with a known one (4), were identified from the dried rhizome of Actaea cimicifuga L. that was used as traditional Chinese medicine for thousands of years with the Chinese common name of shengma. The structures of the new isolates were established using spectroscopic methods, including NMR, mass, UV, and IR spectra. The inhibition activity of compounds 1, 2, and 4 against pancreatic lipase was evaluated.
Keywords: Actaea cimicifuga L.; shengma; Ranunculaceae; monoterpene; cimicifugolides A−C; traditional Chinese medicine